Early treatment with anti-tumor necrosis factor agents improves long-term effectiveness in symptomatic stricturing Crohn's disease. Issue 9 (November 2020) - Rodríguez-Lago, Iago; Hoyo, Javier Del; Pérez-Girbés, Alexandre; Garrido-Marín, Alejandro; Casanova, María José; Chaparro, María; Fernández-Clotet, Agnès; Castro-Poceiro, Jesús; García, María José; Sánchez, Sara; Ferreiro-Iglesias, Rocío; Bastón, Iria; et al.
Background: There is limited evidence on the effectiveness of biological therapy in stricturing complications in patients with Crohn's disease. Aim: The study aims to determine the effectiveness of anti-tumor necrosis factor (TNF) agents in Crohn's disease complicated with symptomatic strictures. Methods: In this multicentric and retrospective study, we included adult patients with symptomatic stricturing Crohn's disease receiving their first anti-TNF therapy, with no previous history of biological, endoscopic or surgical therapy. The effectiveness of the anti-TNF agent was defined as a composite outcome combining steroid-free drug persistence with no use of new biologics or immunomodulators, hospital admission, surgery or endoscopic therapy during follow-up. Results: Overall, 262 patients with Crohn's disease were included (53% male; median disease duration, 35 months, 15% active smokers), who received either infliximab ( N  = 141, 54%) or adalimumab ( N  = 121, 46%). The treatment was effective in 87% and 73% of patients after 6 and 12 months, respectively, and continued to be effective in 26% after a median follow-up of 40 months (IQR, 19–85). Nonetheless, 15% and 21% of individuals required surgery after 1 and 2 years, respectively, with an overall surgery rate of 32%. Postoperative complications were identified in 15% of patients, with surgical site infection as the most common. Starting anti-TNF therapy in the first 18 months after the diagnosis of Crohn's disease or the identification of stricturing complications was associated with a higher effectiveness (HR 1.62, 95% CI 1.18–2.22; and HR 1.55, 95% CI 1.1–2.23; respectively). Younger age, lower albumin levels, strictures located in the descending colon, concomitant aminosalicylates use or presence of lymphadenopathy were associated with lower effectiveness. Conclusions: Anti-TNF agents are effective in approximately a quarter of patients with Crohn's disease and symptomatic intestinal strictures, and 68% of patients are free of surgery after a median of 40 months of follow-up. Early treatment and some potential predictors of response were associated with treatment success in this setting.